P-type doping of zinc oxide by metal-organic chemical vapor deposition - Sun, Xiaowei. (2008)
In this project, we investigated the growth and post-growth annealing treatment of ZnO thin films, deposited by a home-made metal organic chemical vapor deposition (MOCVD), which was set up with the support of this project. The growth of the ZnO thin films was studied with various growth parameters and reactor designs. With the first generation of MOCVD, the pre-reaction of precursors in gaseous phase has greatly influenced the ZnO thin films deposited with the original reactor. In order to obtain high quality film, the MOCVD reactor and growth process have been systematically modified to eliminate the pre-reaction of the precursors. Using the modified reactor and growth process, highly c-axis oriented polycrystalline ZnO thin films were obtained.